Diffuse-Type Tenosynovial Giant Cell Tumour Involving Bone Masquerading as Langerhans Cell Histiocytosis - Florence M. F. Cheung; Timothy Y. C. So; Tony H. T. Sung; Ying-Lee Lam (Case Reports in Medicine)
We presented a case of diffuse-type tenosynovial giant cell tumour (DTSGCT) of foot masquerading as Langerhans cell histiocytosis. Preliminary diagnosis by needle biopsy was difficult due to the major involvement of bones and the overshadowing effect of the accompanying Langerhans cells. The complete curettage specimen with relevant immunohistochemistry and molecular tests made the final diagnosis of DTSGCT possible. The biomolecular mechanism for the masquerading phenomenon was explained by CSF1 overexpression in the neoplastic cells attracting migration and proliferation of CSF1R-positive Langerhans cells.